Pengaruh Struktur Aktiva, Ukuran, Likuiditas dan Profitabilitas terhadap Struktur Modal Emiten Sektor Ritel di Bursa Efek Indonesia (Sebuah Pengujian Hipotesis Pecking Order) - Sienly Veronica Wijaya; Bram Hadianto (Jurnal Akuntansi, 2008)
The aim of this research is to examine pecking order hypothesis with some variables that have the impact on capital structure. Some variables that we used are asset tangibility firm ’s size, liquidity, and profitability. The sample that we used was taken from retail 's issuer sector which selected by purposive sampling method. Regression analysis with pooled data was conducted in this research as analysis method. The result states liquidity is theonly variable that support pecking order hypothesis. In addition, this variabel also have the greatest impact on capital structure.Keywords: liquidity, capital structure